Implications for modeling anion exchange treatment of perfluoroalkyl substances in drinking water and related natural organic impacts: a pilot study - Samantha J. Smith; David G. Wahman; Eric J. Kleiner; Brooke N. Gray; Toby T. Sanan; Eva K. Stebel; Cameron X. Gastaldo; Esther W. Hughes; Sophia G. Pedigo; Boris Datsov; Malcolm F. Lathrop-Allen; Isabella L. Bass; et al. (Water Research, 2026)

Terrestrial Laser Scanning for the Estimation of Above Ground Biomass of Mangrove Roots by Modelling Them as Inverted Trees - Hamish Asmath; John Agard; Toby Jackson; Nikia Gooding; Gerard Alleng; Graham King; Michael Oatham; Farrah Mathura (Wetlands, 2025)
The complex root systems of mangroves such as Rhizophora spp. can hold up to 40% of the total tree biomass yet have usually been neglected in the assessment of the aboveground biomass (AGB). Traditional measurements of AGB can be laborious, costly, time consuming, and require the destruction of the tree. Terrestrial laser scanning (TLS) has increasingly been applied to recreate the architecture of trees to reduce the need for destructive sampling. Modelling Rhizophora mangle L. prop and aerial roots as inverted trees allowed recreation of the volumes using a largely automated methodology. Trees were scanned using a Leica (Switzerland) BLK360 TLS, scans registered and combined, individual tree point clouds extracted and cleaned, the root and trunk point clouds automatically disaggregated, the branches and leaf point cloud separated using auto segmentation techniques, and finally then the volume of the woody fraction of the tree generated in TreeQSM. Two trees were scanned and destructively harvested to assess the modelled wood volume and weight. Wood volume was overestimated by 6.18 and 8.31%, while AGB was overestimated by 2.07 and 2.93%. The robustness of these results demonstrate that this methodology can be applied to improve the estimation of mangrove aboveground biomass. It can facilitate the development of site and species specific allometric equations, that would contribute towards the improved accuracy of carbon estimates at the landscape scale.

Tall Bornean forests experience higher canopy disturbance rates than those in the eastern Amazon or Guiana shield - Toby D. Jackson; Fabian J. Fischer; Grégoire Vincent; Eric B. Gorgens; Michael Keller; Jérôme Chave; Tommaso Jucker; David A. Coomes (Global Change Biology, 2024)
The future of tropical forests hinges on the balance between disturbance rates, which are expected to increase with climate change, and tree growth. Whereas tree growth is a slow process, disturbance events occur sporadically and tend to be short‐lived. This difference challenges forest monitoring to achieve sufficient resolution to capture tree growth, while covering the necessary scale to characterize disturbance rates. Airborne LiDAR time series can address this challenge by measuring landscape scale changes in canopy height at 1 m resolution. In this study, we present a robust framework for analysing disturbance and recovery processes in LiDAR time series data. We apply this framework to 8000 ha of old‐growth tropical forests over a 4–5‐year time frame, comparing growth and disturbance rates between Borneo, the eastern Amazon and the Guiana shield. Our findings reveal that disturbance was balanced by growth in eastern Amazonia and the Guiana shield, resulting in a relatively stable mean canopy height. In contrast, tall Bornean forests experienced a decrease in canopy height due to numerous small‐scale (

Wind Shapes the Growth Strategies of Trees in a Tropical Forest - Toby D. Jackson; Paulo Bittencourt; Jakob Poffley; Juliet Anderson; Helene C. Muller‐Landau; Pablo A. R. Ramos; Lucy Rowland; David Coomes (Ecology Letters, 2024)
In tropical forests, trees strategically balance growth patterns to optimise fitness amid multiple environmental stressors. Wind poses the primary risk to a tree's mechanical stability, prompting developments such as thicker trunks to withstand the bending forces. Therefore, a trade‐off in resource allocation exists between diameter growth and vertical growth to compete for light. We explore this trade‐off by measuring the relative wind mortality risk for 95 trees in a tropical forest in Panama and testing how it varies with tree size, species and wind exposure. Surprisingly, local wind exposure and tree size had minimal impact on wind mortality risk; instead, species wood density emerged as the crucial factor. Low wood density species exhibited a significantly greater wind mortality risk, suggesting a prioritisation of competition for light over biomechanical stability. Our study highlights the pivotal role of wind safety in shaping the life‐history strategy of trees and structuring diverse tropical forests.

Plant-soil biodiversity relationships and nutrient retention in agricultural riparian zones of the Sacramento Valley, California - Anna Young-Mathews; Steven W. Culman; Sara Sánchez-Moreno; A. Toby O’Geen; Howard Ferris; Allan D. Hollander; Louise E. Jackson (Agroforestry Systems, 2010)